2019
DOI: 10.1186/s43055-019-0045-4
|View full text |Cite
|
Sign up to set email alerts
|

Trans-arterial embolization of malignant tumor-related gastrointestinal bleeding: technical and clinical efficacy

Abstract: Background: Gastrointestinal (GI) tract bleeding is a major cause of mortality among patients with GI malignancies. We aimed to assess the technical and clinical efficacy of trans-arterial embolization (TAE) as a symptomatic treatment of tumor-related GI bleeding. This study was conducted for patients with GI bleeding secondary to histopathologically proven different GI malignancies. Fourteen patients underwent trans-arterial embolization. Patients were followed up clinically for any complications or episodes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Embolization is a VIT where blood flows are deliberately blocked around the blood vessels of a target lesion via intravascular deposition of embolic agents from catheters for therapeutic purposes [ 4 ]. Previous reports demonstrated that therapeutic endovascular embolization has the potential to treat acute gastrointestinal bleeding, arteriovenous malformations, fistulas, and targeted cancer treatments [ 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Embolization is a VIT where blood flows are deliberately blocked around the blood vessels of a target lesion via intravascular deposition of embolic agents from catheters for therapeutic purposes [ 4 ]. Previous reports demonstrated that therapeutic endovascular embolization has the potential to treat acute gastrointestinal bleeding, arteriovenous malformations, fistulas, and targeted cancer treatments [ 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%